Efektivitas Penggunaan Papan Monopoli Dalam Meningkatkan Penguasaan Kosakata Bahasa Jepang : Studi Eksperimen Terhadap Siswa Kelas XI SMAN 1 Pangalengan - Widasaputra, Annisa Dwi Oktaviani (2013)
Vocabulary is a collection of words that belong to a language which is used to arrange sentence. Vocabulary has an important role in the process of language learning, especially for Japanese language learning. In the process of language learning at schools, the students still has difficulties to learn Japanese vocabulary. As a solution, author gives monopoly board game as a learning media to improve student's ability to remember Japanese vocabulary. the purpose of this research is to; 1) to find out about the student's japanese vocabulary learning outcomes before using monopoly board game. 2 to find out about the student's japanese vocabulary learning outcomes after using monopoly board game. 3) to find out about any significant difference in Japanese vocabulary learning before and after using monopoly board game . 4) to find out student's response about monopoly board game in Japanese vocabulary learning. The method used in this research is quasi experiment. Population of this research are the students of Pangalengan 1 senior high school grade XI. Sample of this research are 20 students of pangalengan 1 senior high school grade XI. Instrument used is a test and questionnaire. From the data analysis, it is known that; 1) average score or mean of student's vocabulary before the treatment (pretest) is 67,8 and mean of student's vocabulary after the treatment (posttest) is 97,25. 2) after the data calculation is it know that t-count>t table. 11,01>2,09 for significance degree of 5% and 11,1>2.86 for significance degree of 1% which is means that the hypothesys of this research (Hk) is accepted. In summary, the significant difference is found between pretest and posttest which is means that the used of monopoly board game as the learning media is effective to improve students ability to remember Japanese vocabulary. Keyword: Game, Monopoly board, vocabulary